Unilateral Scissor Bite Managed with Prefabricated Functional Appliances in Primary Dentition-A New Interceptive Orthodontic Protocol - Chaypat Simsuchin; Yong Chen; Shuying Huang; Sreekanth Kumar Mallineni; Zhihe Zhao; Urban Hagg; Colman McGrath (MDPI AG, 2021)
A unilateral scissor bite is a type of severe malocclusion in primary dentition that can influence the development of the mandible and face. The present case report describes an interceptive treatment on a 4-year-old girl with a unilateral scissor bite combined with an anterior crossbite, increased reverse overjet, and overbite on a skeletal Class III base. The patient was treated with a new Prefabricated Functional Appliance (PFA) which was modified from a Frankel-III appliance to induce a mandible to move backwards and relieve an occlusion discrepancy of the dental arch, and a functional dental rehabilitation with resin and myofunctional exercises with a PFA which was modified from an oral screen appliance were performed during the treatment. The total treatment time was 11 months and a satisfactory improvement of occlusion and facial esthetics was achieved. This case report presents a new PFA system and treatment protocol in primary dentition which results in a favorable outcome, and the clinical effectiveness of this appliance system warrants further investigation.